Endogenous time variation in vector autoregressions - Danilo Leiva-Leon; Luis Uzeda (Bank of Canada, 2020)
We introduce a new class of time-varying parameter vector autoregressions (TVP-VARs) where the identified structural innovations are allowed to influence - contemporaneously and with a lag - the dynamics of the intercept and autoregressive coefficients in these models. An estimation algorithm and a parametrization conducive to model comparison are also provided. We apply our framework to the US economy. Scenario analysis suggests that the effects of monetary policy on economic activity are larger and more persistent in the proposed models than in an otherwise standard TVP-VAR. Our results also indicate that costpush shocks play an important role in understanding historical changes in inflation persistence.
Keywords: C11; C32; E31; E52; 330; Econometric and statistical methods; Transmission of monetary policy; Inflation and prices